Dietary supplementation of hemp oil in teddy dogs: Effect on apparent nutrient digestibility, blood biochemistry and metabolomics. Issue 3 (1st March 2022) - Xin, Guosheng; Yang, Jie; Li, Ruiguo; Gao, Qiaoxian; Li, Ronglin; Wang, Jianguo; Zhang, Juan; Wang, Jing
ABSTRACT: Present study aimed to evaluate the influence of distinct concentration of dietary supplements hemp oil on apparent nutrient digestibility, blood biochemical parameters and metabolomics of teddy dogs. A total of 25 healthy teddy dogs were selected and divided into five treatments according to diet supplements hemp oil at a rate of 0% (A), 0.5% (B), 1% (C), 2% (D), and 4% (E). Appropriate added hemp oil improved apparent nutrient digestibility of dry matter, crude protein and crude fat (86.32–88.08%, 86.87–88.87% and 96.76–97.43%). The hemp oil significantly increased blood biochemical of utilization related total protein, albumin and globulin (61.33–69.54, 35.08–40.38 and 26.53–31.63 g/L), immunity capacity related immunoglobulin E and γ-interferon (203–347kU/L and 23.04–25.78ng/L), energy-related thyroxine and triiodothyronine (27.11–36.75 and 0.94–1.67 nmol/L). In addition, hemp oil improved superoxide dismutation (26.47–33.02 U/ml) and reduced malondialdehyde (5.30–3.28 nmol/ml). The differential metabolites mainly included nucleotides and metabolites of oxidized lipids, bile and other fatty acids, coenzymes and vitamins. The main metabolic pathways included purine and arachidonic acid metabolism, bile and unsaturated fatty acid biosynthesis, cell oxidative phosphorylation and rheumatoid arthritis. Overall, appropriate dietary supplements hemp oil positively to nutrient digestibility and blood metabolism, immunity and antioxidant capacity, 1% to 2% hemp oil supplements was recommended for teddy dog diet. Graphical abstract: uf0001